Demodulation of Interferogram with Closed Fringes Using the Phase Shifting Technique - Marmolejo, H Ulises Rodríguez; Acevedo, Daniel Jauregui; Muñoz, Debani Ximena Rodríguez (Engineering And Technology Journal, 2022)
This research exposes the foundations of optical metrology which occupies one of the most important in optics. A brief description is made of interferometry which in turn is part of the optical metrology. It demonstrates how an interferogram is obtained. It is also explained the way in which one of the most advanced techniques is applied simple in the demodulation of the phase, since the goal of any technique in interferometry is to find the term “phase” which refers to the physical quantity to be measured whether effort, displacement, distance, pressure, temperature, velocity, shape, dimensions, etc; since it is not possible to achieve it by the conventional methods. The phase obtained in the present article corresponds to the image (interferogram) of a pattern of closed fringes of a lens, which uses a technique called phase shift that consists of acquiring several interferograms, which in turn lead to a result known as phase wrapped so it is necessary to apply some method phase unwrapping to obtain the solution.